Concept maps in introductory statistics. (23rd July 2015) - Witmer, Jeffrey A.
Summary: Concept maps are tools for organizing thoughts on the main ideas in a course. I present an example of a concept map that was created through the work of students in an introductory class and discuss major topics in statistics and relationships among them.